ICTs and Speed Learning in Special Education: High-Consciousness Training Strategies for High-Capacity Learners through Metacognition Lens - Mitsea, Eleni; Drigas, Athanasios; Skianis, Charalabos (Technium Social Sciences Journal, 2022)
Education in the 21st century is called upon to prepare students with disabilities to enter a high-consciousness society where people can learn, think and react fast. The current review paper aims at investigating the role of fast learning in special education. We trace the essential indicators of speed learning with a special focus on those factors that are most relevant to learning disabilities. Afterward, we present evidence-based training techniques and strategies that speed up learning. In addition, we examine the role of ICTs as essential training tools in speed learning. Finally, we discuss the role of metacognition in training fast and conscious learners. The results of this review showed that speed learning training techniques improve all those factors that accelerate learning such as spatial attention, visual span, processing speed, speed reaction, executive functions, metacognition and consciousness. Most important, fast learning strategies meliorate control processes and spatial intelligence which is extremely fast and powerful. This study also points to the option of including high-speed training techniques in schools to help children with or without disabilities to become conscious and high-capacity learners.